Combined therapy with probiotic VSL#3 and Omega-3 fatty acids attenuates colonic injury and inflammation in chronic DNBS-induced colitis in mice - Yoldaş İlktaç, Havvanur; Kızıltan, Gül; Devrim Lanpir, Aslı; Ozansoy, Mehmet; Günal, Mehmet Yalçın; Özmen Togay, Sine; Keskin, İlknur; Özdemir, Ekrem Musa; Kılıç, Ülkan (Polish Academy of Sciences, 2021)
Inflammatory bowel disease (IBD) is a progressive chronic inflammatory disease affecting the gastrointestinal tract with a chronic relapsing and remitting disease course. While there are a number of therapeutic strategies available to treat IBD, a definitive treatment still hasn't been defined, leading to alternative treatment options including nutritional support. Herein, we planned to investigate the combined impact of probiotics and omega-3 (omega-3) fatty acids on inflammatory response and intestinal epithelium in chronic colitis induced by 2,4-Dinitrobenzenesulfonic acid (DNBS). Fifty BALB/c mice were randomly divided into five groups: non-colitis control, colitis with no treatment applied (control colitis), colitis treated with probiotics (VSL#3), colitis treated with omega-3, and colitis treated with both VSL#3 and omega-3. Colitis was induced by intrarectal administration of 2,4-Dinitrobenzenesulfonic acid (DNBS) in all groups but the non-colitis control group. Ten days after the DNBS period, phosphate-buffered saline (for both the non-colitis control and colitis control groups), VSL#3, omega-3, or VSL#3 + omega-3 treatments were administered intragastrically to their respective groups for 10 days. By analyzing the colonic expression of interleukin IL-6, IL-10, and IL-17A, and interferon gamma (IFN-gamma) and tumor necrosis factor alpha (TNF-alpha) levels, results revealed that levels of IFN-gamma IL-17, and TNF-alpha were significantly higher in the control colitis group when compared with the other groups. The control colitis, colitis +VSL#3, and colitis + omega-3 groups exhibited higher scores of microscopic damage compared to the non-colitis control and colitis + VSL#3 + omega-3 groups. The closest histological image to the non-colitis control group was presented in the colitis + VSL#3 + omega-3 group. The findings indicate that the combined effect of probiotics and omega-3 fatty acids might have a protective effect against colon injury and inflammation by creating synergistic effects. However, more research is needed to understand the exact mechanism of this synergistic effect and to examine how this therapeutic approach can be used in inflammatory bowel diseases.
Keywords: Cytokines; Strains; Essential Fatty Acids; Inflammatory Bowel Diseases; Colonic Tissue